Environmental governance of the great seas : law and effect - DiMento, Joseph F.; Hickman, Alexis Jaclyn (Cheltenham, UK : Edward Elgar, 2012)
The great seas contain immense resources and provide invaluable services to humankind, yet their environmental conditions are threatened world-wide. The authors of this comprehensive study provide a rich assessment of the seas and the efficacy of the initiatives governing them, as well as suggestions for improving governance and protection. Case studies of the Baltic, Mediterranean, Black, Caribbean and East Asian seas illustrate the varying degrees of policy success, failure and promise. The authors address the specific roles of the Law of the Sea and the United Nations Regional Seas Programme and discuss the importance of better information exchange between scientists and policy makers, increased funding, greater participation, and new and more effective laws. National, regional and international initiatives are conceptualized as clusters, and their success evaluated using data on the physical conditions of the seas, the law and policy adopted, and international cooperation. The interdisciplinary, insightful treatment of this complex issue will be of great interest to policymakers, students and scholars in the fields of law and policy as well as marine and environmental sciences. -- Publisher description.
Introduction -- The Baltic Sea / Hermanni Backer, Joseph F.C. DiMento, and Alexis Jaclyn Hickman -- The Black Sea -- The East Asian seas -- The Mediterranean Sea / Tullio Scovazzi, Joseph F.C. DiMento, and Alexis Jaclyn Hickman -- The West and Central African seas -- The wider Caribbean region -- An accounting.
Includes bibliographical references (pages 194-213) and index.
Keywords: Law of the sea; Marine resources -- Government policy